1992
DOI: 10.1073/pnas.89.17.8278
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of C8 alkylation of guanine residues by activated arylamines: evidence for initial adduct formation at the N7 position.

Abstract: Aromatic amines are bioactivated to electrophilic compounds that react with DNA, predominantly at the Ca position of guani bases. This site is weakly nudeephilic and it has been proposed that the Cs adduct Is the final product after initial N7-adduct formation. To consider this possibility, we reacted several C-substituted nine derivatives with N-acetoxy-2-aminofluorene, prepared in situ from 2-acetylsalicylic acid and N-hydroxy-2-aminofluorene. With C5,N'-dimethylguanine, an adduct was isolated in good yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 13 publications
3
134
2
Order By: Relevance
“…Guanyl-N7 intermediates have been proposed to be involved in the formation of dG-C8 arylamine DNA adducts (60). The initial bond formation occurs as a hydrazo linkage between the NH 2 position of the arylamine and the N7 atom of guanine, followed by rearrangement to the more stable dG-C8 adduct; alternatively, the adduct can undergo depurination.…”
Section: Discussionmentioning
confidence: 99%
“…Guanyl-N7 intermediates have been proposed to be involved in the formation of dG-C8 arylamine DNA adducts (60). The initial bond formation occurs as a hydrazo linkage between the NH 2 position of the arylamine and the N7 atom of guanine, followed by rearrangement to the more stable dG-C8 adduct; alternatively, the adduct can undergo depurination.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of a dG-N7-IQ adduct in this work provides new information to clarify the formation mechanism of the dG-C8-IQ adduct, considering the generation of dG-N7 in a first step, followed by a possible rearrangement leading to the dG-C8 adduct. Therefore, the rearrangement mechanism reported in Scheme 5 can be reasonably proposed for the formation of both dG-N7-IQ and dG-C8-IQ, based on the mechanism initially suggested by Humphreys et al for the C8 alkylation of guanine by activated arylamines [28]. In addition, this mechanism represents the only way to explain the formation of a dG-N7 adduct without considering the destabilization of the glycosidic bond leading to a depurination process.…”
Section: Scheme 2 Formation Mechanisms Proposed For Fragment Ions Obmentioning
confidence: 99%
“…Generally, dG-N7 adducts are not stable and rapidly undergo decomposition reactions, mainly depurination [26,27], which have not been observed during our work. On the other hand, dG-N7 adducts have already been synthesized with arylamines and were stable enough to be characterized by NMR [28] and a linkage of PhIP with the N7 atom of dG has also been proposed for a minor adduct detected in vivo in rat [24]. Besides, dG-C8 adducts can also find their origin (at least partially) in a rearrangement process occurring on initial dG-N7 adducts, in particular when a nitrenium ion represents the electrophilic species leading to adduct formation [29 -31].…”
Section: Scheme 2 Formation Mechanisms Proposed For Fragment Ions Obmentioning
confidence: 99%
“…Another strong electrophile, a nitrenium ion (RϪ NH ϩ ) arising from hydroxylamine, has been reported to react with 2Ј-deoxyguanosine to form an adduct at C-8 along with several other products including 8-oxo-dGuo (30,31). These studies also suggested that an N-7 adduct cation is first formed as an intermediate by the reaction of dGuo with RϪNH ϩ , followed by arylamine migration from N-7 to C-8 to form the C-8 arylamine adduct (30,31). Higher yields of 8-Cl-Guo under alkaline conditions (Fig.…”
Section: Table I Effect Of Ferrous and Ferric Ions On Hocl-mediated Fmentioning
confidence: 99%